ECTHR_COMMITTEE 62459/09 vom 2. Mai 2013 , AFFAIRE GOUDOUMAS c. GRÈCE - Ecthr Committee (2013)
Violation de l'article 6 - Droit à un procès équitable (Article 6 - Procédure administrative;Article 6-1 - Délai raisonnable); Violation: 6;6-1